PENGARUH AKUPRESUR TERHADAP NYERI PUNGGUNG PADA IBU HAMIL DI KLINIK UTAMA BUNDA RIA KOTA BANDA ACEH - Nurul Husna; Eva Zulisa; Cut Mainy Handiana (Jurnal Medicare, 2025)
Back pain in pregnant women can be managed pharmacologically using analgesic drugs and non-pharmacologically through methods such as birth ball exercises, prenatal yoga, endorphin massage, warm compresses, deep breathing relaxation, and acupressure. This study aimed to determine the effect of acupressure on back pain in pregnant women at Klinik Utama Bunda Ria, Banda Aceh, in 2024. The research design was a quasi-experimental study with a one-group pretest-posttest method. The population consisted of 960 pregnant women, with a sample of 15 participants. The study was conducted from July 22 to July 29, 2025. Data were analyzed using Chi-square and paired t-tests through SPSS. The results showed that before acupressure, most respondents (80%) experienced moderate pain. After acupressure, there was a significant reduction in pain levels (ρ = 0.000). In conclusion, acupressure had a significant effect in reducing back pain in pregnant women. It is recommended that healthcare workers improve services, provide information, and conduct health education for third-trimester pregnant women regarding the prevention and management of back pain.